Analysis to Select Filter Media and The Treatment Effect of Non-point Pollution Source in Road Runoff - Lee, Tae Goo; Han, Young Hae (KIEAE Journal, 2014)
This study selected and analyzed filter media that can be applied in non-point pollution reduction devices aimed at processing the source of pollution on site for road runoff that increases rapidly in rainfall-runoff in order to improve the water quality of urban areas. First, the factors that affect the quality of runoff caused by sources of non-point pollution include physical and social factors such as the usage of land around the area of water collection, type of pavement and movement of cars and people, as well as rainfall characteristics such as frequency, intensity, amount and duration of rainfall. Second, the purification tests of the filter media were processed for pH, BOD, COD and T-P, and the filter media showed to have initial purification effect at that items. However, the filter media showed to be very effective for the processing of SS, T-N, Zn and Cd from the beginning to the end. Third, for filter media, zeolite and vermiculite showed to be effective for processing SS, T-N, Zn and CD constantly, and composite filter media including zeolite showed to have strong processing effects. The authors conclude that this study can be applied to technical areas and policies aimed at reducing non-point pollution in urban areas and can also contribute to allowing eco-friendly management of rainfall as well as improvement of water quality. KCI Citation Count: 0